Oral health research with children - ZOE MARSHMAN & MELANIE J. HALL (IAPD and Blackwell, 2008)
Over the past 30 years, the position of children in society has changed with increasing recognition of children’s rights and the need to involve them in decisions about their education, and social and health care.